A method for preparing a spotted brick and a spotted brick
By applying low-light wear-resistant base glaze and wear-resistant fine glaze on the blank of the spotted bricks and performing firing treatment, the problem of poor anti-slip and wear-resistant performance of spotted bricks in the prior art is solved, and high resistance is achieved Grinding and high anti-slip effects.
Patent Information
- Application Number
- CN202310858869.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-12
AI Technical Summary
In the prior art, spotted brick products that apply fine glaze have poor anti-slip and wear resistance.
By pressing the blank powder into molding, applying low-light wear-resistant base glaze and wear-resistant fine glaze to form a base glaze layer and a fine glaze layer, and then firing it on the fine glaze layer to obtain spotted bricks .
It greatly improves the wear resistance and anti-slip performance of spotted bricks, and can achieve wear resistance level 4, 2100 rpm or above and anti-slip performance German standard R9 or above.
Smart Images

Figure CN116924682B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of spotted bricks, and in particular to a spotted brick preparation method and the spotted bricks. Background Art
[0002] At present, the mainstream fine full-body brick products on the market generally apply a layer of cosmetic soil on the blank first, then inkjet decoration, and finally apply fine glaze to achieve a fine feel. Since the fine glaze is applied after the decorative printing, it must be ensured that the fine glaze has sufficient transparency to achieve a clear pattern decoration effect. It is precisely because of the process limitations of transparent fine glaze that the spotted brick products on the market with fine glaze generally feel smooth, have low Mohs hardness, low wear resistance, and low anti-slip grade, that is, the anti-slip performance and wear resistance are poor.
[0003] Therefore, the prior art has defects and needs to be improved and developed. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing spotted bricks and spotted bricks in response to the above-mentioned defects of the prior art, aiming to solve the problem that the spotted brick products with fine glaze applied in the prior art have poor anti-slip performance and wear resistance.
[0005] The technical solution adopted by the present invention to solve the technical problem is as follows:
[0006] A method for preparing a spotted brick, comprising:
[0007] Pressing the green body powder into shape to obtain a spotted brick green body;
[0008] Applying a low-gloss wear-resistant base glaze on the spotted brick body to form a base glaze layer, and applying a wear-resistant fine glaze on the base glaze layer to form a fine glaze layer;
[0009] The fine glaze layer is subjected to pattern decoration treatment to obtain a pattern decoration layer, and the spotted brick body to which the pattern decoration layer has been applied is subjected to firing treatment to obtain a spotted brick.
[0010] In one embodiment, the chemical composition of the low-gloss wear-resistant base glaze, measured in mass percentage, includes:
[0011] SiO2 55-65%, Al2O3 20-25%, CaO 4-6%, MgO 0-2%, Na2O 4-6%, K2O2-4%, ZnO0-2%, BaO 4-6%, ZrO2 3-5%;
[0012] The chemical composition of the wear-resistant fine glaze, measured in mass percentage, includes:
[0013] SiO2 45-55%, Al2O3 15-20%, CaO 5-10%, MgO 4-8%, Na2O 3-6%, K2O 1-3%, ZnO 2-5%, BaO 10-15%, ZrO2 1-3%.
[0014] In one embodiment, the raw materials of the low-gloss wear-resistant base glaze include, by mass percentage:
[0015] Zirconium silicate 9%, potassium feldspar 25%, sodium feldspar 28%, calcined kaolin 6%, Indonesian kaolin 8%, frit powder 13%, desiliconized aluminum 6%, wollastonite 5%;
[0016] The raw materials of the wear-resistant fine glaze include, by mass percentage:
[0017] Calcined zinc oxide 2%, barium carbonate 10%, zirconium silicate 3%, potassium feldspar 13%, sodium feldspar 18%, desiliconized aluminum 7%, calcined talc 4%, Indonesian kaolin 7%, quartz powder 3%, dolomite 13%, frit powder 20%.
[0018] In one embodiment, the steps of preparing the zirconium silicate include:
[0019] The zirconium silicate industrial waste residue is ball-milled and then subjected to secondary calcination processing;
[0020] 50 zirconium with a zirconium content of 50% is screened out from the zirconium silicate industrial waste slag processed by secondary calcination, and the composite zirconium remaining after calcination and impurity removal;
[0021] The mixture of the 50 zirconium and the composite zirconium is used as the raw material for the low-gloss wear-resistant base glaze and the wear-resistant fine glaze.
[0022] In one embodiment, the chemical composition of the zirconium 50, in terms of mass percentage, includes:
[0023] SiO2 25.65%, Al2O3 19.58%, CaO 0.55%, MgO 0.42%, Na2O 2.41%, K2O0.82%, Fe2O3 0.21%, ZrO2 50.36%;
[0024] The chemical composition of the composite zirconium, measured in mass percentage, includes:
[0025] SiO2 26.6%, Al2O3 38.5%, CaO 0.6%, MgO 0.5%, Na2O 2.9%, K2O 0.7%, Fe2O30.5%, ZrO2 29.7%.
[0026] In one embodiment, the green body powder comprises, by mass percentage:
[0027] Coffee spot powder 15-25%, green spot powder 25-35%, gray spot powder 20-30%, white spot powder 25-35%;
[0028] The particle sizes of the coffee speckle powder, the green speckle powder, the grey speckle powder and the white speckle powder are all 0.3-1 mm.
[0029] In one embodiment, after pressing the green body powder into a shape to obtain a spotted brick green body, the method further comprises:
[0030] The spotted brick body is dried at a drying temperature of 80-130° C. and a drying time of 40-60 minutes;
[0031] After the spotted brick body is dried, the surface of the spotted brick body is dusted and cleaned;
[0032] The dust-removed and cleaned spotted brick bodies are sprayed with water at a rate of 70-71 g / m2 to keep the temperature of the spotted brick bodies at 60-80°C.
[0033] In one embodiment, a low-gloss wear-resistant base glaze is applied on the spotted brick body to form a base glaze layer, and a wear-resistant fine glaze is applied on the base glaze layer to form a fine glaze layer, comprising:
[0034] Applying a low-gloss wear-resistant base glaze on the spotted brick body in a bell-shaped glaze pouring manner, with a glazing specific gravity of 1.80-1.88 and a glazing amount of 500-600 g / m2 to form a base glaze layer;
[0035] A wear-resistant and fine glaze is applied on the base glaze layer in a bell-jar glazing manner, with a glazing specific gravity of 1.80-1.88 and a glazing amount of 500-600 g / m2 to form a fine glaze layer.
[0036] In one embodiment, pattern decoration is performed on the fine glaze layer to obtain a pattern decoration layer, and the spotted brick body to which the pattern decoration layer is applied is fired to obtain a spotted brick, comprising:
[0037] Performing screen printing, rubber roller printing or inkjet printing on the fine glaze layer to obtain a pattern decoration layer;
[0038] The spotted brick body to which the pattern decoration layer has been applied is fired at a temperature of 1150-1250° C. for 35-55 minutes to obtain a spotted brick.
[0039] The present invention also provides a spotted brick, wherein the spotted brick is prepared by the spotted brick preparation method as described above.
[0040] The invention discloses a method for preparing a spotted brick and a spotted brick. The method comprises: pressing a body powder to obtain a spotted brick body; applying a low-light wear-resistant base glaze on the spotted brick body to form a base glaze layer; applying a wear-resistant fine glaze on the base glaze layer to form a fine glaze layer; performing a pattern decoration process on the fine glaze layer to obtain a pattern decoration layer; and performing a firing process on the spotted brick body to which the pattern decoration layer has been applied to obtain a spotted brick. The invention replaces the conventional cosmetic soil and transparent glaze system by continuously applying the low-light wear-resistant base glaze and the wear-resistant fine glaze, thereby greatly improving the wear resistance and anti-skid performance of the spotted brick. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a flow chart of a preferred embodiment of the method for preparing spotted bricks in the present invention. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0043] At present, the market lacks fine wear-resistant and non-slip full-body tiles that can achieve low cost, low resource consumption, high wear resistance, and high anti-slip level through conventional ordinary process flow. Research on the preparation process technology of fine wear-resistant and non-slip full-body spotted tiles can reduce manufacturing costs and improve product quality from the source of production technology, and improve the quality of full-body tile products in terms of fineness, anti-slip, and wear resistance.
[0044] The mainstream fine glaze on the market generally adopts a cosmetic soil + transparent glaze system, which achieves a high and delicate feel by lowering the melting temperature of the transparent glaze, but has a low Mohs hardness, low wear resistance, and low anti-skid grade. The present invention adopts a special anti-skid and wear-resistant base glaze and a fine glaze formula, preferably an opalescent glaze system, and does not use a transparent glaze system. Increasing the proportion of elements such as calcium, barium, aluminum, and zirconium in the formula greatly improves the wear resistance and anti-skid performance of fine full-body brick products, and can achieve fine and wear-resistant full-body bricks with both anti-skid and wear-resistant properties under a high and delicate feel, with a wear resistance of more than 2100 revolutions of the national standard level 4, and an anti-skid performance of more than German standard R9, thereby solving the problem of poor wear resistance and low anti-skid performance of fine full-body bricks.
[0045] The present invention can effectively reduce the moisture of the product entering the kiln during firing by adopting a method of applying glaze twice in succession before inkjet decorative printing, and eliminates the process of applying transparent glaze after inkjet decoration and the process of baking in a drying kiln, thereby effectively reducing the consumption of natural gas energy, thereby solving the problem of high energy consumption of fine, wear-resistant and non-slip spotted bricks.
[0046] The present invention introduces 50 zirconium, calcined composite zirconium, calcium carbonate and other materials into the base glaze and fine glaze formula to replace the existing zirconium silicate, aluminum oxide and other materials for whitening. The whiteness is high, the cost is low, and the hand feel is good. The comprehensive cost is reduced by 30%, achieving low cost and high quality performance, and the market competitiveness is greatly improved, thereby solving the problem of high comprehensive cost of fine, wear-resistant and non-slip spotted bricks.
[0047] See also Figure 1 , Figure 1 Flow chart of the method for preparing spotted bricks in the present invention. Figure 1 As shown, the method for preparing the spotted bricks according to the embodiment of the present invention comprises the following steps:
[0048] Step S100, pressing the green body powder into shape to obtain a spotted brick green body.
[0049] In one implementation, the green body powder includes, by mass percentage, 15-25% coffee spot powder, 25-35% green spot powder, 20-30% gray spot powder, and 25-35% white spot powder; the particle sizes of the coffee spot powder, green spot powder, gray spot powder, and white spot powder are all 0.3-1 mm.
[0050] Specifically, the green powder of this embodiment is composed of four kinds of spots, and the particle size of the spot powder is 0.3-1 mm. The types of spots are determined by product requirements, including but not limited to four kinds of spots such as coffee, green, gray, and white (or other colors). The basic formula of the spot powders of various colors is the same, only the types and quantities of various colorants added are different, so as to show spots of different colors. White spots will be whitened by adding some additional aluminum oxide and zirconium silicate.
[0051] In one embodiment, the basic formula of the spotted powder includes, in percentage by mass: 5% Yongyang magnesia, 12% station white mud, 22% Jintai ball clay, 4% bentonite, 12% Xiaolou white mud, 7% sodium sand No. 1, 20% Ningshi powder, 7% Hui sodium sand, 2% polishing tailings, and 9% Kangxin sodium sand.
[0052] The chemical composition of Yongyang magnesia, in terms of mass percentage, includes: ignition loss 4.5%, SiO2 67.23%, Al2O3 2.87%, Fe2O3 1.2%, CaO 0.28%, MgO 23.5%, K2O 0.17%, and Na2O 0.2%.
[0053] The chemical composition of the station white mud, expressed in mass percentage, includes: loss on ignition 7.63%, SiO2 65.82%, Al2O3 23.92%, Fe2O3 0.69%, CaO 0.16%, MgO 0.21%, K2O 0.98%, and Na2O 0.35%.
[0054] The chemical composition of Jintai ball clay, in terms of mass percentage, includes: loss on ignition 9.34%, SiO2 56.08%, Al2O331.20%, Fe2O3 1.12%, CaO 0.15%, MgO 0.23%, K2O 1.36%, and Na2O0.26%.
[0055] The chemical composition of bentonite, in terms of mass percentage, includes: loss on ignition 6.21%, SiO2 68.28%, Al2O3 18.2%, Fe2O3 1.82%, CaO 1.33%, MgO 0.37%, K2O 2.65%, and Na2O 0.56%.
[0056] The chemical composition of Xiaolou white mud, in terms of mass percentage, includes: loss on ignition 7.05%, SiO2 65.48%, Al2O3 22.59%, Fe2O3 1.92%, CaO 0.21%, MgO 0.13%, K2O 1.58%, and Na2O 0.23%.
[0057] The chemical composition of sodium sand No. 1, in terms of mass percentage, includes: loss on ignition 1.85%, SiO2 70.56%, Al2O3 20.08%, Fe2O3 0.65%, CaO 0.67%, MgO 0.48%, K2O 1.05%, and Na2O 2.86%.
[0058] The chemical composition of Ningshi powder, in terms of mass percentage, includes: ignition loss 1.32%, SiO2 72.75%, Al2O3 16.9%, Fe2O3 0.42%, CaO 0.63%, MgO 0.89%, K2O 0.79%, and Na2O 5.12%.
[0059] The chemical composition of Huina sand, in terms of mass percentage, includes: ignition loss 0.98%, SiO2 74.45%, Al2O3 14.52%, Fe2O3 0.12%, CaO 0.69%, MgO 0.23%, K2O 0.67%, and Na2O 7.53%.
[0060] The chemical composition of the polishing tailings, in terms of mass percentage, includes: ignition loss 1.35%, SiO2 72.53%, Al2O3 18.65%, Fe2O3 0.85%, CaO 0.95%, MgO 0.41%, K2O 2.12%, and Na2O 2.24%.
[0061] The chemical composition of Kangxin sodium sand, in terms of mass percentage, includes: loss on ignition 1.35%, SiO2 72.12%, Al2O3 17.15%, Fe2O3 0.22%, CaO 0.15%, MgO 0.21%, K2O 1.52%, and Na2O 6.29%.
[0062] In one embodiment, after step S100, the method further includes:
[0063] Step S10, drying the spotted brick body at a drying temperature of 80-130° C. and a drying time of 40-60 minutes;
[0064] Step S20, after the spotted brick body is dried, the surface of the spotted brick body is dusted and cleaned;
[0065] Step S30, spraying the dust-removed and cleaned spotted brick bodies with water at a rate of 70-71 g / m2 to keep the temperature of the spotted brick bodies at 60-80°C.
[0066] Specifically, after the body is dried, two dust removal fans are used to remove dust from the body surface, and a small amount of water is applied for cooling so that the temperature of the spotted brick body is at 60-80°C, so as to facilitate the application of low-gloss wear-resistant base glaze and wear-resistant fine glaze to the body surface.
[0067] like Figure 1 As shown, the method for preparing spotted bricks according to the embodiment of the present invention further comprises the following steps:
[0068] Step S200: applying a low-gloss wear-resistant base glaze on the spotted brick body to form a base glaze layer, and applying a wear-resistant fine glaze on the base glaze layer to form a fine glaze layer.
[0069] In one implementation, the chemical composition of the low-gloss wear-resistant base glaze is measured in mass percentage and includes: SiO255-65%, Al2O3 20-25%, CaO 4-6%, MgO 0-2%, Na2O 4-6%, K2O 2-4%, ZnO 0-2%, BaO4-6%, and ZrO2 3-5%. After the body is cleaned, a layer of low-gloss wear-resistant base glaze slurry is first applied for glaze decoration to fill the pores on the surface of the body. The matte wear-resistant base glaze applied at this stage is not a cosmetic soil in the traditional sense. Its melting temperature is lower than that of the cosmetic soil, and its anti-fouling performance is better than that of the cosmetic soil. The low-gloss wear-resistant base glaze has the properties of low gloss (gloss 3 degrees), good whiteness (whiteness above 55 degrees), good wear resistance (level 4 above 2100 revolutions), and good anti-fouling performance, so that the prepared fine wear-resistant, anti-skid and anti-fouling spotted bricks can achieve multiple properties such as good whiteness, low gloss, high wear resistance, and anti-fouling.
[0070] The chemical composition of the wear-resistant fine glaze of this embodiment is calculated by mass percentage, including: SiO2 45-55%, Al2O3 15-20%, CaO 5-10%, MgO 4-8%, Na2O 3-6%, K2O 1-3%, ZnO 2-5%, BaO 10-15%, ZrO2 1-3%. The wear-resistant fine glaze applied in this embodiment has anti-fouling, anti-skid, wear-resistant and other properties. The matte fine wear-resistant glaze slurry applied in this project can achieve the glaze anti-skid performance of German standard R9 or above, anti-fouling performance level 3, wear resistance level 4 and more than 2100 revolutions. The anti-skid, anti-fouling and wear-resistant fine glaze can achieve multiple properties such as anti-fouling, anti-skid, and high wear resistance.
[0071] Compared with the conventional fine full-body tile preparation process, the key technical principle of the present invention is to replace the original cosmetic soil and transparent fine glaze process by using opaque base glaze and opaque fine glaze process. In the conventional process, the cosmetic soil has a high melting temperature, while the transparent fine glaze has a low melting temperature. The difference in melting temperatures between the two is large, and problems such as glaze pinholes, poor wear resistance, and poor anti-skid performance are very likely to occur during firing. The present invention adopts opaque base glaze and opaque fine glaze process without using cosmetic soil, so that the two not only have similar melting temperatures and are more closely combined, but also introduce a large amount of calcium, barium, aluminum, zirconium and other elements into the formula of the two, which greatly improves the wear resistance and anti-skid performance of the fine full-body tile products.
[0072] In one embodiment, the step S200 specifically includes:
[0073] Step S210, applying a low-gloss wear-resistant base glaze on the spotted brick body in a bell-shaped glaze pouring manner, with a glazing specific gravity of 1.80-1.88 and a glazing amount of 500-600 g / m2 to form a base glaze layer;
[0074] Step S220, applying a wear-resistant fine glaze on the base glaze layer in a bell-jar glazing manner, with a glazing specific gravity of 1.80-1.88 and a glazing amount of 500-600 g / m2 to form a fine glaze layer.
[0075] Specifically, if the low-gloss wear-resistant base glaze and the wear-resistant fine glaze are applied continuously at a very close time interval, pinholes and bubble defects are likely to occur. Therefore, after the base glaze decoration, it is necessary to apply the wear-resistant fine glaze after a certain interval, about 30 seconds. If it is on the production line, the wear-resistant fine glaze can be applied at a distance of 15 meters, so that the low-gloss wear-resistant base glaze can be fully penetrated when applied to the body, and the residual moisture on the surface is low, so that the fine glaze can be applied more tightly and with fewer defects.
[0076] This embodiment can effectively reduce the moisture of the product entering the kiln during firing by applying glaze twice in succession before inkjet decorative printing, eliminates the conventional process of applying transparent glaze after inkjet decoration, eliminates the drying kiln baking process, effectively reduces natural gas energy consumption, and greatly reduces manufacturing costs.
[0077] In one embodiment, the raw materials of the low-gloss wear-resistant base glaze include, by mass percentage, 9% zirconium silicate, 25% potassium feldspar, 28% sodium feldspar, 6% calcined kaolin, 8% Indonesian kaolin, 13% frit powder, 6% desiliconized aluminum, and 5% wollastonite. The raw materials of the wear-resistant fine glaze include, by mass percentage, 2% calcined zinc oxide, 10% barium carbonate, 3% zirconium silicate, 13% potassium feldspar, 18% sodium feldspar, 7% desiliconized aluminum, 4% calcined talc, 7% Indonesian kaolin, 3% quartz powder, 13% dolomite, and 20% frit powder. In this embodiment, a large amount of calcium, barium, aluminum, zirconium and other elements are introduced into the formula of the low-gloss wear-resistant base glaze and the wear-resistant fine glaze, which greatly improves the wear resistance and anti-slip performance of the fine full-body tile products.
[0078] In one embodiment, the chemical composition of the frit powder is expressed in mass percentage, including: SiO2 50.7%, Al2O3 19.6%, Fe2O3 0.1%, CaO 11.1%, MgO 2.7%, Na2O 4.2%, K2O 1.0%, TiO2 0.1%, ZnO 1.7%, B2O3 0.3%, BaO 8.0%. Specifically, the frit powder used as the raw material for the low-gloss wear-resistant base glaze and the wear-resistant fine glaze is a high-aluminum frit, which is used to replace part of the aluminum oxide. The fired glaze surface is very smooth, which improves the delicate feel. Commonly used frits are generally low-aluminum frits for melting or high-expansion coefficient frits for adjusting brick types.
[0079] In one implementation, the preparation steps of the zirconium silicate include: ball milling the zirconium silicate industrial waste slag and then performing a secondary calcination process; screening out 50 zirconium with a zirconium content of 50% and the composite zirconium remaining after calcination and impurity removal from the zirconium silicate industrial waste slag that has undergone the secondary calcination; and using the mixture of the 50 zirconium and the composite zirconium as the raw material for the low-gloss wear-resistant base glaze and the wear-resistant fine glaze.
[0080] Specifically, this embodiment purchases industrial waste slag from a zirconium silicate factory, performs ball milling and secondary calcination processing, screens out 50 zirconium with a zirconium content of 50%, and the remaining composite zirconium after calcination and impurity removal, and adds them into the formula to replace the existing zirconium silicate and alumina. It is low-priced and can digest industrial waste slag.
[0081] In one embodiment, the chemical composition of the zirconium 50, in terms of mass percentage, includes:
[0082] SiO2 25.65%, Al2O3 19.58%, CaO 0.55%, MgO 0.42%, Na2O 2.41%, K2O0.82%, Fe2O3 0.21%, ZrO2 50.36%; the chemical composition of the composite zirconium, in mass percentage, includes: SiO2 26.6%, Al2O3 38.5%, CaO 0.6%, MgO 0.5%, Na2O 2.9%, K2O 0.7%, Fe2O3 0.5%, ZrO2 29.7%.
[0083] Specifically, by adopting a special glaze basic formula and rationally adjusting calcium, barium, aluminum and zirconium, the delicate full-body tile products have both high wear resistance (wear resistance level 4 above 2100 revolutions), high anti-slip properties (anti-slip performance German standard R9 or above) and high anti-fouling properties (anti-fouling level 3) while having a delicate feel.
[0084] like Figure 1 As shown, the method for preparing spotted bricks according to the embodiment of the present invention further comprises the following steps:
[0085] Step S300, performing pattern decoration treatment on the fine glaze layer to obtain a pattern decoration layer, and performing firing treatment on the spotted brick body to which the pattern decoration layer has been applied to obtain a spotted brick.
[0086] In one embodiment, the step S300 specifically includes:
[0087] Step S310, performing screen printing, rubber roller printing or inkjet printing on the fine glaze layer to obtain a pattern decoration layer;
[0088] Step S320, firing the spotted brick body to which the pattern decoration layer has been applied at a firing temperature of 1150-1250° C. for 35-55 minutes to obtain a spotted brick.
[0089] Specifically, this embodiment adjusts the pattern texture and pattern color effect on the surface of the tile through screen printing decoration, rubber roller printing decoration, inkjet printing decoration, etc., and decorates the overall color of the tile surface.
[0090] The present invention achieves the following effects:
[0091] First, the production process has been streamlined. The two consecutive glazing methods before inkjet decorative printing can effectively reduce the moisture of the product entering the kiln during firing, eliminate the drying kiln baking process, effectively reduce natural gas energy consumption, and streamline the spotted brick production process and the corresponding equipment, personnel and other investments, save energy consumption, and reduce wastewater and exhaust emissions.
[0092] Second, industrial waste slag is used for secondary processing and calcination to screen out 50 zirconium with a zirconium content of 50%, and the remaining composite zirconium after calcination and impurity removal replaces the existing purchased zirconium silicate and alumina materials in the industry. There is no need to purchase zirconium silicate and alumina, which greatly reduces the manufacturing cost, achieves low-cost and high-quality performance, and greatly improves market competitiveness.
[0093] Third, by purchasing industrial waste slag for secondary calcination processing, we can reduce costs while actively digesting industrial waste slag. We no longer need to rely on the mining of zirconium silicate or alumina ore, which protects the environment and reduces the consumption and waste of raw ore resources.
[0094] Fourth, the whole body spotted bricks are delicate, wear-resistant, non-slip and anti-fouling. They have a delicate feel, high wear resistance, good non-slip performance, good anti-fouling effect, low cost and high quality, and can quickly fill the market gap and meet market demand.
[0095] The present invention also provides a spotted brick, wherein the spotted brick is prepared by the spotted brick preparation method as described above.
[0096] The present invention provides a method for preparing a spotted brick and a spotted brick. The method comprises: pressing a body powder into a shape to obtain a spotted brick body; applying a low-light wear-resistant base glaze on the spotted brick body to form a base glaze layer, applying a wear-resistant fine glaze on the base glaze layer to form a fine glaze layer; performing a pattern decoration process on the fine glaze layer to obtain a pattern decoration layer, and performing a firing process on the spotted brick body to which the pattern decoration layer has been applied to obtain a spotted brick. The present invention replaces the conventional cosmetic soil and transparent glaze system by continuously applying the low-light wear-resistant base glaze and the wear-resistant fine glaze, thereby greatly improving the wear resistance and anti-slip performance of the spotted brick.
[0097] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a spotted brick, characterized in that: include: Pressing the green body powder into shape to obtain a spotted brick green body; Applying a low-gloss wear-resistant base glaze on the spotted brick body to form a base glaze layer, and applying a wear-resistant fine glaze on the base glaze layer to form a fine glaze layer; Performing pattern decoration treatment on the fine glaze layer to obtain a pattern decoration layer, and performing firing treatment on the spotted brick body to which the pattern decoration layer has been applied to obtain a spotted brick; The chemical composition of the low-gloss wear-resistant base glaze, measured in mass percentage, includes: SiO2 55-65%, Al2O3 20-25%, CaO 4-6%, MgO 0-2%, Na2O 4-6%, K2O2-4%, ZnO 0-2%, BaO 4-6%, ZrO2 3-5%; wherein the sum of the mass percentages of the various chemical components of the low-gloss wear-resistant base glaze is 100%; The chemical composition of the wear-resistant fine glaze, measured in mass percentage, includes: SiO2 45-55%, Al2O3 15-20%, CaO 5-10%, MgO 4-8%, Na2O 3-6%, K2O 1-3%, ZnO 2-5%, BaO 10-15%, ZrO2 1-3%.
2. The method for preparing spotted bricks according to claim 1, characterized in that: The raw materials of the low-gloss wear-resistant base glaze include, by mass percentage: Zirconium silicate 9%, potassium feldspar 25%, sodium feldspar 28%, calcined kaolin 6%, Indonesian kaolin 8%, frit powder 13%, desiliconized aluminum 6%, wollastonite 5%; The raw materials of the wear-resistant fine glaze include, by mass percentage: Calcined zinc oxide 2%, barium carbonate 10%, zirconium silicate 3%, potassium feldspar 13%, sodium feldspar 18%, desiliconized aluminum 7%, calcined talc 4%, Indonesian kaolin 7%, quartz powder 3%, dolomite 13%, frit powder 20%.
3. The method for preparing spotted bricks according to claim 2, characterized in that: The preparation steps of the zirconium silicate include: The zirconium silicate industrial waste residue is ball-milled and then subjected to secondary calcination processing; 50 zirconium with a zirconium content of 50% is screened out from the zirconium silicate industrial waste slag processed by secondary calcination, and the composite zirconium remaining after calcination and impurity removal; The mixture of the 50 zirconium and the composite zirconium is used as the raw material for the low-gloss wear-resistant base glaze and the wear-resistant fine glaze.
4. The method for preparing spotted bricks according to claim 3, characterized in that: The chemical composition of the zirconium 50 is expressed in mass percentage and includes: SiO2 25.65%, Al2O3 19.58%, CaO 0.55%, MgO 0.42%, Na2O 2.41%, K2O 0.82%, Fe2O3 0.21%, ZrO2 50.36%; The chemical composition of the composite zirconium, measured in mass percentage, includes: SiO2 26.6%, Al2O3 38.5%, CaO 0.6%, MgO 0.5%, Na2O 2.9%, K2O 0.7%, Fe2O30.5%, ZrO2 29.7%.
5. The method for preparing spotted bricks according to claim 1, characterized in that: The green body powder comprises, by mass percentage: Coffee spot powder 15-25%, green spot powder 25-35%, gray spot powder 20-30%, white spot powder 25-35%; The particle sizes of the coffee speckle powder, the green speckle powder, the grey speckle powder and the white speckle powder are all 0.3-1 mm.
6. The method for preparing spotted bricks according to claim 1, characterized in that: After the green body powder is pressed into shape to obtain a spotted brick green body, the method further comprises: The spotted brick body is dried at a drying temperature of 80-130° C. and a drying time of 40-60 minutes; After the spotted brick body is dried, the surface of the spotted brick body is dusted and cleaned; The dust-removed and cleaned spotted brick bodies are sprayed with water at a rate of 70-71 g / m2 to keep the temperature of the spotted brick bodies at 60-80°C.
7. The method for preparing spotted bricks according to claim 1, characterized in that: Applying a low-gloss wear-resistant base glaze on the spotted brick body to form a base glaze layer, and applying a wear-resistant fine glaze on the base glaze layer to form a fine glaze layer, including: Applying a low-gloss wear-resistant base glaze on the spotted brick body in a bell-shaped glaze pouring manner, with a glazing specific gravity of 1.80-1.88 and a glazing amount of 500-600 g / m2 to form a base glaze layer; A wear-resistant and fine glaze is applied on the base glaze layer in a bell-jar glazing manner, with a glazing specific gravity of 1.80-1.88 and a glazing amount of 500-600 g / m2 to form a fine glaze layer.
8. The method for preparing spotted bricks according to claim 1, characterized in that: Performing pattern decoration treatment on the fine glaze layer to obtain a pattern decoration layer, and performing firing treatment on the spotted brick body to which the pattern decoration layer has been applied to obtain the spotted brick, comprising: Performing screen printing, rubber roller printing or inkjet printing on the fine glaze layer to obtain a pattern decoration layer; The spotted brick body to which the pattern decoration layer has been applied is fired at a temperature of 1150-1250° C. for 35-55 minutes to obtain a spotted brick.
9. A spotted brick, characterized in that: The spotted brick is prepared by the spotted brick preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Soft light glaze, soft light glazed ceramic rock plate and preparation method of soft light glazed ceramic rock plate
CN114276016A